Associations of body composition with incident dementia in older adults: Cardiovascular Health Study‐Cognition Study. Issue 10 (17th August 2020) - Cui, Chendi; Mackey, Rachel H.; Shaaban, C. Elizabeth; Kuller, Lewis H.; Lopez, Oscar L.; Sekikawa, Akira
Abstract: Introduction: A body of literature reported associations between late‐life general adiposity measures (eg, body mass index) and dementia. Little is known about the association of late‐life body composition with dementia risk. Methods: We determined this association among cognitively normal participants from the Cardiovascular Health Study‐ Cognition Study. Body composition was assessed by dual‐energy x‐ray absorptiometry in 1994‐1995. Dementia was ascertained at annual follow‐up from 1998‐1999 to 2013. Associations of body composition with incident dementia were assessed by the Fine‐Gray model. Result: Among 344 participants (mean age 78, 62.2% women), body composition was significantly different between men and women, despite similar body mass indexes (BMIs). Increased dementia risk was significantly associated with lower lean mass in men and marginally with low appendicular lean mass in women. Discussion: Decreased lean mass was an indicator of increased dementia risk in older adults. Studies should test whether preventing lean mass loss in older adults reduces dementia risk.